The effects of new Alibernet red wine extract on nitric oxide and reactive oxygen species production in spontaneously hypertensive rats - Kondrashov, Alexey; Vranková, Stanislava; Dovinová, Ima; Sevčík, Rudolf; Parohová, Jana; Barta, Andrej; Pecháňová, Olga; Kovacsová, Maria (Oxidative medicine and cellular longevity, 2012)
We aimed to perform a chemical analysis of both Alibernet red wine and an alcohol-free Alibernet red wine extract (AWE) and to investigate the effects of AWE on nitric oxide and reactive oxygen species production as well as blood pressure development in normotensive Wistar Kyoto (WKY) and spontaneously hypertensive rats (SHRs). Total antioxidant capacity together with total phenolic and selected mineral content was measured in wine and AWE. Young 6-week-old male WKY and SHR were treated with AWE (24,2 mg/kg/day) for 3 weeks. Total NOS and SOD activities, eNOS and SOD1 protein expressions, and superoxide production were determined in the tissues. Both antioxidant capacity and phenolic content were significantly higher in AWE compared to wine. The AWE increased NOS activity in the left ventricle, aorta, and kidney of SHR, while it did not change NOS activity in WKY rats. Similarly, increased SOD activity in the plasma and left ventricle was observed in SHR only. There were no changes in eNOS and SOD1 expressions. In conclusion, phenolics and minerals included in AWE may contribute directly to increased NOS and SOD activities of SHR. Nevertheless, 3 weeks of AWE treatment failed to affect blood pressure of SHR.
Keywords: minerály; superoxiddismutasa; Rats; víno; Antioxidants; superoxiddismutasa 1; Hypertension; reaktivní formy kyslíku; Aorta; polyfenoly; mužské pohlaví; aorta; potkani inbrední SHR; srdeční komory; rostlinné extrakty; Nitric Oxide Synthase Type III; krysa rodu Rattus; Polyphenols; antioxidancia; Superoxide Dismutase; Vitis; Reactive Oxygen Species; Superoxide Dismutase-1; Wine; zvířata; oxid dusnatý; Nitric Oxide; Heart Ventricles; synthasa oxidu dusnatého, typ III; ledviny; hypertenze; Rats, Inbred WKY; Kidney; Plant Extracts; Rats, Inbred SHR; Minerals; potkani inbrední WKY; Male; Animals